Abolishing Youth Justice Systems: Children First, Offenders Nowhere. (April 2021) - Case, Stephen; Haines, Kevin
The 1980s decade of diversion in UK youth justice consolidated critiques of iatrogenic systemic contact and generated an abolitionist momentum that was significantly reversed by the 1990s punitive turn and 'new youth justice' strategies of modernisation, expansionism, interventionism and risk management. However, the tentative rejection of risk management and the rebirth of diversion in contemporary youth justice offer new hope for abolitionist arguments. This article critically evaluates contemporary abolitionist arguments, asserting that Children First definitions and diversionary, Bureau model responses could coalesce to form an innovative paradigm to replace traditional, formal conceptions of youth justice 'systems'.